Os sentidos do adoecer: refazendo o percurso Freudiano - Reis, Inês Maria de Oliveira (2008)
By referring to a psychoanalytic approach,this reaserch proposes a bibliographic rewiew about the signs of sickness: remaking the Freud investigation,choosing as goals to investigate the meanings of psychological diseases, their mecanisms and psychological manifestations involved in the scope of neurotic diseases.The methodology is based on a qualitative reseach done by the analysis of content of a total of 75 selected summaries. In each of these summaries, the meanings of the content are reseached. Ten articulated the areas were chosen:sickness, pulsion, life/death, pain/suffering, loss/mourning, symptom, trauma, narcisism, compulsion to repetition, body, being emphasized the following areas: sickness, pulsion, symptom and body.The reseach points out the relation between the psychological sickness and the opression of the lust,reflecting the existance of the mecanism of sickness and the formation of the symptom.The process of sickness involves a lack of sexual desire, and also a misfunction in the living of the pulsions of life and death, and this fragmentation leads to partial pulsions. The destinies of the pulsions suggest a connection with the psychological sickness,causing pathological manifestations like traumatic neurosis,compulsion to repetition,force of resistences,neurotic contents and their state of morbid suffering.